HYDROGELS MICRO COMPOSITES BASED ON POLYVINYL ALCOHOL/BENTONIT - A. Zainal Abidin; Y. Andre Situmorang; Irwan Noezar (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency)
HYDROGELS MICRO COMPOSITES BASED ON POLYVINYL ALCOHOL/BENTONITE. Hydrogels micro composite for biomedical application has been synthesized from polyvinyl alcohol (PVA) with degree of hydrolyzed 98-99% and bentonite as reinforcement using freeze and thawing technique with 3 cycles. Sodium bentonite used has been sized to 305 nm in average using planetary ball mill. Variation of bentonite composition used in the synthesis are 2.5%, 5%, 10% and 15%w. The hydrogel had been analyzed for its common properties such as gel fraction, Equilibrium Degree of Swelling (EDS), Equilibrium Water Content (EWC) and Water Vapor Transmission Rate (WVTR). While its chemical structure was identified using Fourier Transform-Infra Red (FT-IR) Spectrophotometer and its morphology was characterised using Scanning Electron Microscope (SEM) and X-Ray Diffractometer (XRD). Additionally, its thermal properties were analyzed using Differential Scanning Calorimetry (DSC), and its mechanical properties were tested by tensile machine. Effect of bentonite composition from 0 %w to 15 %w in hydrogel micro composite is decreasing the water absorption capacity from 67.79 % to 52.17 % and increasing the gel fraction from 78.43 % to 94.48 %. As more bentonite added, the composite strength increases by increase in tensile stress from 2.18 MPa to 3.48 MPa, while the water vapor transmission rate decreases from 53.07 g/m2h to 34.42 g/m2h. The hydrogel micro composite melting point does not change with the bentonite addition, i.e. in the range of 230-235 oC, but its glass transition temperature (Tg) increases from 127.8 oC for 0 %w to 147.2 oC for 5 %w.